A multi-agent model of changes in urban safety livability. (June 2020) - Lihu, Pan; Xiaowen, Li; Shipeng, Qin; Yingjun, Zhang; Huimin, Yan
Urban livability is an important factor in decisions regarding modern urban construction. Based on multi-agent modeling theory, a model of the changes in urban safety livability is proposed to analyze the present situation and the trends in urban safety livability in complex urban systems. Considering safety as an example, five environmental indicators, namely public security, fire protection, traffic, emergency response, and residence, are selected. The interactive dynamic feedback mechanisms among resident decision-making behaviors and urban safety livability in the context of these five indicators and relevant policies are provided. A simulation of the changes in urban safety livability is implemented based on resident behaviors. The results show that the multi-agent modeling method is effective for analyzing urban safety livability and can provide decision support for urban development planning.